Interpretation of Soft Skills in Archives - DM Rachmaningsih,; Wijayanti,; Surya Adi Sasmita,; Herwati D Utami, (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2022)
To meet the demands of the workplace, archivists need to understand how soft skills develop. Digital technology development is a task that needs to be accelerated right away. This article attempts to discuss the findings of studies on how archivists work from home (WFH) during the COVID-19 pandemic in Indonesia led to developing soft interpretative skills. A case study approach was employed in this descriptive qualitative research. Questionnaires and interviews were used as the primary data-collecting methods for samples from the local government, the business sector, and ANRI. The findings demonstrated that the perception of soft skills has evolved into an implicative function rather than a meaning-based one. Based on the study's findings, it was determined that soft skills provide an essential and crucial purpose, precisely the demand for digital literacy. It was also determined that the implementation of WFH during the COVID-19 pandemic demonstrated the use of digital literacy abilities.